A new concept of a pseudo-Janus structure: employing a Yin-Yang fish structure film with up/down conversion fluorescence and bi-anisotropic conduction to represent the pseudo-Janus structure as a case study. Issue 25 (8th June 2020) - Qi, Haina; Xie, Yunrui; Yang, Xiuling; Yang, Liu; Ma, Qianli; Tian, Jiao; Yu, Wensheng; Li, Dan; Liu, Guixia; Dong, Xiangting
Abstract : The pseudo-Janus structure is advanced and the Yin-Yang fish structure film is employed to represent the pseudo-Janus structure as a case study. Abstract : The Yin-Yang fish, a sign of traditional Chinese culture, has been widely used to represent the combination of two different properties or the transformation between them in the field of materials chemistry. Inspired by the Yin-Yang fish sign, we propose herein a concept of a structure very different from the Janus structure in materials chemistry, and it is defined as a pseudo-Janus structure. The pseudo-Janus structure can be regarded as a new structure, which is obtained by flipping one side of the Janus structure vertically. The symmetry of the pseudo-Janus structure is different from that of the Janus structure. For the Janus structure, the symmetries are mirror and π symmetry. For the pseudo-Janus structure, the symmetries are central and π symmetry. The Yin-Yang fish sign is a typical pseudo-Janus structure. Herein, employing the Yin-Yang fish structure film representing the pseudo-Janus structure as a case study, we have fabricated a pseudo-Janus structure film (defined as PF) with multi-mode fluorescence and bi-anisotropic conductivity by electrospinning. The two fish-like structural regions of PF are constructed by Janus nanoribbons, and the two eye-like regions consist of nanofibers. The PF achieves a macro-partition of four independent functional domains to obtain excellent synchronous bi-anisotropic conduction, up- and down-conversion multi-mode luminescence to avoid harmful mutual interferences. The Janus nanobelt, realizing a micro-partition of two functional domains, is used as a building unit to construct fish-like regions to microscopically reduce detrimental influences among different functions by isolating and confining them in their own domains, and thus ensuring high conductive anisotropy and strong fluorescence. The micro-partition and macro-partition are highly integrated in the pseudo-Janus structure film to achieve excellent multi-functionality. The pseudo-Janus structural design is also applicable to the construction of other multi-functional materials with different structures or properties.